The development of a protocol for diagnosing hand dermatitis from photographic images - Parsons, Vaughan; Williams, Hywel; English, John; Llewellyn, Joanne; Ntani, Georgia; Madan, Ira (Wiley, 2018)
Background: A hand photography protocol was needed to ascertain the presence and severity of dermatitis in a trial testing the effectiveness of a behaviour change intervention to prevent hand dermatitis in nurses. Methods: We developed the protocol in three stages: (i) established a procedure for collecting hand photographs; (ii) conducted a stepwise validation process to agree rules for diagnosing and determining severity of hand dermatitis and; (iii) trained a research nurse to screen out ‘clear’ cases. Results: We developed and trained fieldworkers (n=97) in a procedure for collecting hand photographs. Study dermatologists established interpretation rules to diagnose and determine the severity of dermatitis from photographs. Prior to the establishment of the rules, inter-observer agreement between the two dermatologists on the presence or absence of hand dermatitis was moderate (kappa 0.5). At the final stage of the validation process, the dermatologists agreed on 88% cases from independent assessments, with consensus reached for the remaining 12% following joint deliberation. Following training, a subgroup analysis of 250 cases screened by the nurse and characterised as ‘clear’ found two (0.8%) ‘positive’ cases were missed. Conclusion: We have developed a hand photography protocol, which may be used in other studies or in hand dermatitis health surveillance programmes.